Edukasi Keamanan Siber Berdigital dengan Aman - Surbakti, Feliks Prasepta Sejahtera (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
The rapid development of digital technology in Indonesia has heightened the need for cybersecurity education to safeguard individuals against prevalent digital fraud. This community service initiative, titled